Study on Treatment of Ciprofloxacin in Water with Co, N Co-doped TiO2 Photocatalysts on Vermiculite - Thuong, Dau Thi; Hong, Tran Thi; Hue, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1, 2024)
This paper presents the results of the treatment of ciprofloxacin in water with Co, N-doped TiO 2 photocatalysts on a vermiculite background. Vermiculite (Ver) material after activation with HNO 3 at three concentrations of 10%, 30%, and 40% exhibits a rougher surface. The 40% HNO 3 activated material has the higest porosity and has a surface area greater than 79.4 times the total surface area of ​​the raw material. Co- and N-doped TiO 2 photocatalysts on vermiculite were prepared by sol-gel method, using a mixture of tetraisopropylorthotitanate Ti(OC 3 H 7 ) 4 (TTIP), ethanol (EtOH), diethanolamine C 4 H 11 NO 2 (DEA), and Co(NO 3 ) 2. 6H 2 O. The influence of doped cobalt on the structure, surface morphology, and photocatalytic properties of N,Cox-TiO 2 /Ver (x=0.04;0.06;0.08 mol) was studied through scanning electron microscopy (SEM) and UV-Vis absorption spectroscopy. The SEM image shows that anatase-TiO 2 crystals are evenly coated on the surface of Ver and the spherical particles are evenly dispersed on the surface of the material. The absorption spectrum shows that the band gap of the sample N,Cox-TiO 2 /Ver (x=0.04, 0.06, 0.08 mol) decreases from 3.32 eV to 2.64 eV. We implemented the preliminary experiments to test the efficiency of our synthesized material to treat the antibiotic ciprofloxacin in hospital wastewater. N,Co 0,08 -TiO 2 /Ver materials showed over 80% efficiency of removing the ciprofloxacin in these hospital wastewater samples.